PENGENDALIAN PEMBANGUNAN PERUMAHAN DI KAWASAN PERBUKITAN KOTA SEMARANG - S Sunarti; Ratna Aurelia (Diponegoro University, 2012)
Around the beginning of 2000, there was the phenomenon of increased residential development in the hills of Semarang. Development undertaken by the developer, had less attention to rules and policies regarding the determination of residential location. This study aims to formulate an alternative form of residential development control in the hills of Semarang. The results of this study is pre-shaped housing development control action and action to control post. Pre control action in the form of licensing should be accordance with the spatial supported by the zoning regulations, developers have incorporated a business, an area of at least 1 hectare plot of land, reinforced by AMDAL. The post-action control of its control of the first warning letter, the second warning and if not heeded the warnings given immediate cessation of all four of the action execution of work or demolition. The recommendations in this study each party in carrying out his duties in accordance with rules established and approved by the region.